Oviposition preference and larval development of the invasive moth Cydalima perspectalis on five European box‐tree varieties. (22nd October 2012) - Leuthardt, F. L. G.; Baur, B.
Abstract The box‐tree pyralid Cydalima perspectalis (Walker 1859) (Lepidoptera: Pyralidae), native to Eastern Asia, is a newly introduced species causing severe damage to box‐trees (Buxus sp.) in private and public gardens as well as in semi‐natural box‐tree forests in Central Europe. It is so far not known whether different box‐tree subspecies (or varieties) are similarly affected by this invasive moth. In a choice experiment offering branches of five different box‐tree varieties as oviposition sites, we found a preference of female moths for laying their egg clusters on the variety 'Rotundifolia', while other varieties were less frequently considered. The preference for 'Rotundifolia', the variety with the largest leaves in the tests, remained when intervariety differences in foliar area (mean leaf size × number of leaves) were taken into account. Feeding larvae on leaves of either of the five box‐tree varieties revealed a significant effect of the seasonal generation of C. perspectalis on the growth rate of individuals but no influence of the box‐tree variety. Larvae from the spring generation show the highest growth rate, those from the summer generation a moderate and those from the autumn generation the lowest growth rate. The moths used in the experiments may belong to the 10th to 12th generation present in Europe. The time elapsed since their introduction may be too short for an optimal adaptation to the partly novel diet encountered by the invasive moth.